2005
DOI: 10.1097/01.ico.0000154411.07315.0a
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Fluoroquinolones Against Mycobacterium abscessus and Mycobacterium chelonae Causing Infectious Keratitis After LASIK in Brazil

Abstract: Fluoroquinolone MICs for 17 M. abscessus and M. chelonae isolates recovered from infectious keratitis cases in Brazil indicate that they are not susceptible to these drugs in vitro. Further studies to investigate the in vivo effectiveness of fluoroquinolones against mycobacteria are required because in vitro tests do not support their use in the treatment of micobacterial keratitis in this particular geographic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 65 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…In Brazil, a study of multiple outbreak-causing mycobacterial keratitis isolates found in vitro resistance to fourth-generation fluoroquinolones in nearly all isolates tested; however, correlation with clinical response to treatment was not performed. 23 Although MICs are important in vitro indicators of antibiotic activity, they do not necessarily predict in vivo antibiotic efficacy, especially for topical antibiotic agents. In vitro MICs are of limited value in predicting clinical success for topical antibiotic agents because the MIC breakpoints are based on the pharmacokinetics of systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a study of multiple outbreak-causing mycobacterial keratitis isolates found in vitro resistance to fourth-generation fluoroquinolones in nearly all isolates tested; however, correlation with clinical response to treatment was not performed. 23 Although MICs are important in vitro indicators of antibiotic activity, they do not necessarily predict in vivo antibiotic efficacy, especially for topical antibiotic agents. In vitro MICs are of limited value in predicting clinical success for topical antibiotic agents because the MIC breakpoints are based on the pharmacokinetics of systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This case reports the emergence of a fourth-generationfluoroquinolone-resistant atypical mycobacteria post-LASIK surgery. Combined with other recent reports (Hö fling-Lima et al 22 and Freitas et al 23 ), our report may herald an emerging ominous trend of fourth-generation fluoroquinolone resistance. Factors that may contribute to the emergence of this resistance are their increasingly widespread use and, specifically, their extensive use perioperatively in LASIK and other ophthalmic surgeries.…”
Section: Discussionmentioning
confidence: 57%
“…5 However, in vivo data have not been systematically investigated and the number of cases tested in vitro is limited. There is contradictory evidence in the literature on the in vitro sensitivity of the pathogen to moxifloxacin.…”
Section: Discussionmentioning
confidence: 99%